2022
DOI: 10.1002/prca.202100099
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of proteome changes in plasma of HIV‐infected patients receiving antiretroviral therapy

Abstract: Purpose Antiretroviral therapy (ART) prevents human immunodeficiency virus (HIV)‐1 onward transmission and disease progression, leading to excellent prognosis in people living with HIV‐1 (PWH). However, side effects, complications, and impaired immune reconstitution persist in some patients treated with ART. We aimed to profile proteome changes in plasma before and after ART to identify the molecular pathways altered by ART. Experimental Design Quantitative proteomics analysis based on tandem mass tag (TMT) la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The results from this study illustrated the underlying mechanistic pathways in response to ART and identified potential targets to prompt the immune reconstitution. [5] Zhang et al explored the O-glycoproteome changes in the serum of 10 breast cancer patients using isobaric-TMT-labeling quantitative O-glycoproteomics. 299 O-glycopeptides corresponding to 83 Oglycosites and 66 O-glycoproteins were identified.…”
Section: He Et Al Reviewed the Advances Of Proteomics Technologies In...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results from this study illustrated the underlying mechanistic pathways in response to ART and identified potential targets to prompt the immune reconstitution. [5] Zhang et al explored the O-glycoproteome changes in the serum of 10 breast cancer patients using isobaric-TMT-labeling quantitative O-glycoproteomics. 299 O-glycopeptides corresponding to 83 Oglycosites and 66 O-glycoproteins were identified.…”
Section: He Et Al Reviewed the Advances Of Proteomics Technologies In...mentioning
confidence: 99%
“…The results from this study illustrated the underlying mechanistic pathways in response to ART and identified potential targets to prompt the immune reconstitution. [ 5 ]…”
mentioning
confidence: 99%